The interaction between cyclin B1 and cytomegalovirus protein kinase pUL97 is determined by an active kinase domain - Steingruber, Mirjam; Socher, Eileen; Hutterer, Corina; Webel, Rike; Bergbrede, Tim; Lenac, Tihana; Sticht, Heinrich; Marschall, Manfred (Viruses, 2015)
Replication of human cytomegalovirus (HCMV) is characterized by a tight virus-host cell interaction. Cyclin-dependent protein kinases (CDKs) are functionally integrated into viral gene expression and protein modification. The HCMV-encoded protein kinase pUL97 acts as a CDK ortholog showing structural and functional similarities. Recently, we reported an interaction between pUL97 kinase with a subset of host cyclins, in particular with cyclin T1. Here, we describe an interaction of pUL97 at an even higher affinity with cyclin B1. As a striking feature, the interaction between pUL97 and cyclin B1 proved to be strictly dependent on pUL97 activity, as interaction could be abrogated by treatment with pUL97 inhibitors or by inserting mutations into the conserved kinase domain or the nonconserved C-terminus of pUL97, both producing loss of activity. Thus, we postulate that the mechanism of pUL97-cyclin B1 interaction is determined by an active pUL97 kinase domain.
Keywords: Active conformation; CDK ortholog; Cyclin B; Human cytomegalovirus; Kinase activity; Mode of kinase-cyclin interaction; Protein kinase pUL97; Protein-protein interaction